Northern border of Mexico: Trashumant exhumations: de-sedimentation of ruins and archives in Autobiography of Cotton, by Cristina Rivera Garza - Rico León, Patricia Georgina (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
In Autobiography of Cotton, Cristina Rivera Garza undertakes a return to a personal and genealogical origin based on the material traces of those social, territorial, and ecological processes that affected—and continue to affect—the northern border of Mexico. In order to examine the multiple temporalities, paths and historical connections that articulate its narrative, this article turns to the concepts of ruins, Derridean hauntology, geological stratification of time in writing, and the attention to the mutability of archives and territory. Analyzing the constellation made up of the different objects and processes that affect the search described in this book, the juxtaposition of two haunting aspects that besiege the same territory stands out: that of a multiple, eroded and sedimented past, and that of the present threat of devastation and violence. Thus, this article studies how the efforts of this narrative to confront the sediments of the past do not follow a restorative perspective; instead, they are presented as an investigative journey attentive to the risks of a present out of joint.
Keywords: geological writings; hauntology; ruins; archive; travel